KOMPOSISI DAN STRUKTUR VEGETASI PENYUSUN ZONASI HUTAN MANGROVE TANJUNG PRAPAT MUDA-TANJUNG BAKAU KABUPATEN KUBU RAYA - Irpan, Filian Basri; manurung, togar fernando; Muflihati, . (JURNAL HUTAN LESTARI, 2017)
Tanjung Prapat Muda-Tanjung Bakau (TPM-TB) mangrove forest in Kubu Raya Regency is a mangrove forest that has been designated as a protected area. TPM-TB mangrove forest area has very high potential diversity of flora and fauna. The analysis of mangrove forest vegetation Tanjung Prapat Muda-Tanjung Bakau (TPM-TB) Kubu Raya Regency aims to determine the composition and structure of vegetation in the TPM-TB mangrove forest. This research used a combined methods of transec and plot line. The results showed that the composition and vegetation structure of the TPM-TB mangrove forest consisted of 10 species from 4 families, namely, Rhizophora apiculata, R. mucronata, Brugueirra parviflora, B. cylndrica, B. gymnorrhiza, Avicennia marina, A. alba, Excoecaria agallocha, Xylocarpus granatum, and X. Muloccensis. Importance Value Index (IVI) which is the highest for seedlings, saplings, and trees was found in Rhizophora apiculata. Dominance Index Value indicated that there was no concentration on one species but on several species. Diversity of species was low but even between species abundance. Distribution structure consisted of 3 distributions, namely Rhizophora, Avicennia, and Brugueirra. Keywords: Analysis Vegetation, Avicennia, Â Batu Ampar, Brugueirra, Rhizophora.